APLIKASI e-CRM BERBASIS WEB PADA RUMAH SAKIT - Wilis Kaswidjanti; Herry Sofyan; Luthfie Hawari (Jurusan Teknik Informatika, 2011)
The purpose of this research is to design an e-CRM application that serves as an Internet-based services for customers or patients to provide information needed by the customer or patient without being limited by distance or time. With the increased competition and technological development is rapidly increasing, then every hospital strives to provide the best service to customers, or patients with a hope to get customers or new patients and retain old customers or patients. One solution that appears is electronic-Customer Relationship Management (e-CRM) is applied by using the Internet and SMS technology. The method used is waterfall method which includes, analysis and systems engineering, requirements analysis, design, programming, testing and maintenance. This application was built using the programming language PHP and MySQL to design database.Hasil achieved from the writing of this research is the application of customer service or patient that provides information (schedule doctor's office, clinic services, patient medical records, consultation and sms notifications check-up), provide member features pages to provide personalized services to customers or patients. With the application of e-CRM customer service Internet-based hospital is expected to maintain good long-term relationship with its customers.